Nurse night shift work and risk of gastrointestinal cancers - Guo, Lin; Li, Xiaojun (Frontiers in Public Health, 2025)
The prevalence of night-shift employment is on the rise among full-time and part-time workers globally. Those engaged in night-shift work encounter various biological challenges, including exposure to artificial light during nighttime and disruptions to their circadian rhythms. These factors, along with changes in daily routines and activities, may pose significant risks to the health of night workers. Notably, the number of individuals working overtime or on night shifts has increased across various sectors, particularly in transportation, healthcare, and manufacturing. The International Agency for Research on Cancer (IARC) has classified night-shift work as probably carcinogenic to humans (IARC Group 2A). Subsequent research has identified several potential mechanisms through which night-shift work may contribute to carcinogenicity: (1) disruption of circadian rhythms, (2) suppression of melatonin levels due to nighttime light exposure, (3) physiological alterations, (4) lifestyle changes, and (5) reduced vitamin D levels resulting from inadequate sunlight exposure. Colorectal cancer (CRC) poses a significant public health challenge, ranking as the second leading cause of cancer-related death worldwide in 2020. Other than CRC, other gastrointestinal cancers are also creating a great global health issue because of their morbidity and mortality rates. In this review, we highlight the role of night shifts in disturbing circadian rhythm and how this action leads to carcinogenesis in the GI tract.